(3eNJUQ GdeYJeO aj CUhd Gdabgs - (3SdjeGf Hf fGUQ Hf SYjOs; (3eMeO Hf Ydj GdWjH GdHUQj, CHh GdMSjf,J (B436 (3g` s ((3eMeO Hf fGUQ Hf SYjO Hf YHO Gddg s)
(3ChdgG (B:s
(3hPcQJe MGWce Gddg HYdeg Cfce CWddJe Ydi cJGH GdeYJeO ai CUhd Gdabg s
(3BNQgG (B:s
(3dcGf MGUdkG acGf jhLO YfO GdWdH s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B275s
Keywords: (3CUhd Gdabgs